2012
DOI: 10.1364/oe.20.019374
|View full text |Cite
|
Sign up to set email alerts
|

Spectral tuning of the phosphorescence from metalloporphyrins attached to gold nanorods

Abstract: The spectral shape of the phosphorescence emission of organometallic porphyrin molecules is shown to be altered when these chromophores are incorporated into hybrid nanostructures with gold nanorods. This result shows that triplet-singlet transitions, which are (at least partially) dipolar forbidden, can be modified by the dipolar resonances of gold nanoparticles. By choosing nanorods of increasing aspect ratios, it is possible to match the long axis plasmon resonance of the nanorods to a specific phosphoresce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Additionally, quenching of luminescence depends on the particle size and shape in the case of porphyrin attachment to gold nanoparticles [40]. The position of the porphyrin fluorescence peak can be affected by combination with noble metals [41,42]. In [43], an attachment of porphyrin to gold clusters through a molecular spacer was reported resulting in suppression of the quenching of the porphyrin excited singlet, as compared to the quenching of self-assembled porphyrins on a two-dimensional flat gold surface.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, quenching of luminescence depends on the particle size and shape in the case of porphyrin attachment to gold nanoparticles [40]. The position of the porphyrin fluorescence peak can be affected by combination with noble metals [41,42]. In [43], an attachment of porphyrin to gold clusters through a molecular spacer was reported resulting in suppression of the quenching of the porphyrin excited singlet, as compared to the quenching of self-assembled porphyrins on a two-dimensional flat gold surface.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies reported to date on plasmon-enhanced fluorescence of porphyrins, or related compounds, focus on multichromophore systems. These include studies on core–shell assemblies composed of metal nanoparticles coated by a layer of porphyrins directly linked to its surface or entrapped in a silica layer. From a different perspective, plasmon-enhanced fluorescence has also been studied on light-harvesting complexes from natural systems that instead of porphyrins comprise chlorophyll pigments. The collective behavior of the multiple chromophores in these systems, such as exciton coupling or energy transfer, bring additional complexity to the evaluation of antenna effects. Therefore, a clear evaluation of plasmon-enhanced fluorescence on individual chromophores would be desirable for a rational design of nanocomposite systems that incorporate porphyrins, and it would allow the assessment of the limits of emission enhancement on a weak emitting molecule.…”
mentioning
confidence: 99%
“…Examples of enhanced ISC and phosphorescence can be found in the literature. Unlike the short-range electron exchange, which is limited to a thin layer adjacent to the metal, the field effects extend for tens of nanometers and could modulate the ISC rate across the entire P3HT@AuNR sample. This is an appealing possibility; however, the acceleration of the ISC and phosphorescence is small, with the highest reported enhancement factor of 2.4, which is much too low to account for the formation of the P3HT triplet on a subpicosecond time scale. If such effects are present in P3HT@AuNR , they are of secondary importance.…”
Section: Resultsmentioning
confidence: 99%